Windows Phone data binding. IN Windows Phone. - Liberty, Jesse
Jesse Liberty shows the strength of XAML programming as he discusses hands-on code for data binding against runtime data, design-time data and binding one control to another.
Keywords: Windows phone (Computer file); Extensible Application Markup Language (XAML).